101 Consecutive Profunda Artery Perforator Flaps in Breast Reconstruction: Lessons Learned with Our Early Experience. Issue 2 (August 2017) - Haddock, Nicholas T.; Gassman, Andrew; Cho, Min-Jeong; Teotia, Sumeet S.
Abstract : Background: Free and local flaps based on the profunda artery perforators were first used for reconstruction of pressure sores, burn contractures, and extremity wounds. Recently, a revised profunda artery perforator flap was introduced for breast reconstruction. However, despite increasing reports of the use of the flap, it remains a rarely used option. The authors present their early experience with the first 101 profunda artery perforator flaps used for breast reconstruction at their institution. Methods: The authors conducted a retrospective review of the first 101 profunda artery perforator flaps at their institution. Patient demographics, perioperative data, and postoperative complications were recorded and analyzed. Results: One hundred one consecutive profunda artery perforator flaps were used to reconstruct 96 breasts in 56 patients. In 42 breasts, the flap was used in conjunction with another flap—with a deep inferior epigastric perforator flap ( n = 36), a superior gluteal artery perforator flap ( n = 1), or as stacked profunda artery perforator flaps ( n = 5). Mean flap weight was 425 g (range, 170 to 815 g), and mean patient body mass index was 26.8 kg/m 2 (range, 18.2 to 42.3 kg/m 2 ). Complications included total flap loss (2 percent), donor-site cellulitis (5.9 percent), and donor-site wound dehiscence (10.9 percent). Conclusions: The profunda artery perforator flap is a safe and reliable option for breast reconstruction. Flap size is adequate for breast reconstruction in appropriately selected patients. Furthermore, it can be combined with other flaps when additional volume or skin requirements are present. Flap and donor-site complications are comparable to those of other free tissue breast reconstruction options. It is a clear second option to the deep inferior epigastric perforator flap for autologous tissue reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.